Bone augmentation and autogenous transplantation of premolar to the site of the fissure in a cleft palate patient - Luvizuto, Eloá R.; Faco, Eduardo F. S.; Faco, Renato S.; Queiroz, Thallita P.; Margonar, Rogerio; Betoni-Júnior, Walter; Camara, Kléryo A. S.; Assunção, Wirley Goncalves [UNESP] (Wiley, 2012)
This article presents a case report of autogenous tooth transplantation to the site of the fissure, in addition to bone augmentation with graft of autogenous bone harvested from the iliac crest, performed in a cleft palate patient, who had insufficient bone volume. A non-syndromic 10-year-old girl, with a unilateral cleft lip and palate, incisal transforamen fissures, agenesis of the maxillary left central incisor and both maxillary lateral incisors, was treated with autogenous bone graft in the cleft area. The orthodontic treatment plan was to replace the missing lateral incisors with the maxillary canines and to extract the mandibular first premolars. One of the mandibular premolars was extracted from its site with 2/3 of its root formation completed and transplanted to the maxillary left central incisor area. After orthodontic treatment, the anatomic crowns were characterized with composite resin. Autogenous tooth transplantation can be performed in the area of the fissure in young cleft palate patients, by performing bone graft augmentation before transplantation of the tooth, to gain sufficient recipient alveolar bone volume. A multidisciplinary approach is mandatory for the success of this clinical procedure, especially in cleft palate patients. © 2012 John Wiley & Sons A/S.
Keywords: Decidous; Exarticulation; Permanent tooth; Treatment